Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Brewer, B. (International Journal of Sports Science & Coaching, 2018)
More of a conversation between colleagues than a formal interview, the discussion between Dr. Gillham and Dr. Jenkins contains numerous kernels of wisdom derived from Dr. Gillham`s professional experiences consulting with coaches and teams. Although many of the situations, decisions, and courses of action described by Dr. Gillham are noteworthy, three aspects are especially deserving of comment: (a) Dr. Gillham`s career path; (b) interrelationships among theory, research, and practice; and (c) insights into effective consulting.